Reward crowdfunding campaigns: Time-to-success analysis - Felipe, Israel (2021)
The time-to-success of reward crowdfunding campaigns constitutes a relevant topic that has been neglected in business literature. In this study, we employ parametric and semi-parametric models of survival analysis to identify the determining factors of the duration of success of these campaigns. Based on more than 4,200 reward crowdfunding campaigns, our results are robust for controls and reveal that the campaigns that attain success most rapidly are located predominantly in cities with greater income inequality. These are cities that are characterized by lower fundraising targets and receive a larger number of pledges. In addition, our covariates indicate a non-constant influence on time-to-success during the fundraising period.